Preparation, FPLC Purification and LC-FT-ICR-MS of Proteins - Tyler Johnson; Jiri Adamec; Paul Blum (Bio-Protocol, 2020)
High magnetic field Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometers provide extremely high mass resolution (resolving power of ~200,000 at 400 m/z) protein detection across a broad mass range, enabling analysis of fine structure of isotopic peak clusters that is missed in other types of mass spectrometers. The protocol detailed here describes preparation of cellular extracts for purification of DNA-binding proteins using multiple chromatographic chemistries via fast protein liquid chromatography (FPLC), and identification and quantitation of the protein isoforms and their post-translational modifications by liquid chromatography coupled to Fourier transform ion cyclotron resonance mass spectrometry (LC-FT-ICR-MS). This protocol benefits from selectively purifying proteins for identification and quantitation by high resolution FT-ICR, which has the resolution to definitively distinguish between acetylation and trimethylation post-translational modification (PTM) additions.